Rare bird documentation form for Peregrine Falcon at Otter Creek Marsh, 1984 - Proescholdt, Bethet al (1984)
Rare bird documentation form for a Peregrine Falcon at Otter Creek Marsh in Tama County, IA on April 29, 1984. Epson - sheet feed